2019
DOI: 10.1111/cag.12571
|View full text |Cite
|
Sign up to set email alerts
|

Bruit aérien et équité environnementale dans les quatre plus grandes métropoles canadiennes

Abstract: Messages clés Respectivement 419 000 et 57 000 personnes résident à l'intérieur des courbes NEF 25 et NEF 30 dans les quatre RMR étudiées, soit des zones de bruit aérien assez élevé. Il y a des situations contrastées en termes d'iniquité selon les métropoles. L'iniquité quant au niveau de bruit aérien mesuré dans le milieu résidentiel est peu prononcée pour les groupes de population étudiés.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…For cumulative noise indicators, the sectors exposed to high noise levels (55–60 and ≥ 60 dB(A)) are mostly located in proximity to urban areas in municipalities adjacent to the Montréal-Trudeau International Airport (Dorval and Pointe-Claire to the west, and the Saint-Laurent district (Bois-Franc neighbourhood) and Ville Mont-Royal to the east). These sectors accommodate mostly wealthy households, owners of single-family multi-storey homes with garages (cottage or bungalow types) and whose purchasing cost is high ( Audrin et al, 2019 ). However, for the high noise levels for the L Amax indicator (65–70 and 70–75 dB(A)), but also at lower noise levels for the L den and L dn indicators (50–55 dB(A)), noise contour areas being greater, within these zones there are certain central neighbourhoods of the Island of Montréal (Villeray–Saint-Michel–Parc-Extension, Côte-des-Neige-Notre-Dame-de-Grâce), as well as surrounding neighbourhoods (Saint-Léonard, Lachine and Ahuntsic-Cartierville), where we find, at least in some parts of these territories, a high proportion of the low-income population ( Ades et al, 2012 , Séguin et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For cumulative noise indicators, the sectors exposed to high noise levels (55–60 and ≥ 60 dB(A)) are mostly located in proximity to urban areas in municipalities adjacent to the Montréal-Trudeau International Airport (Dorval and Pointe-Claire to the west, and the Saint-Laurent district (Bois-Franc neighbourhood) and Ville Mont-Royal to the east). These sectors accommodate mostly wealthy households, owners of single-family multi-storey homes with garages (cottage or bungalow types) and whose purchasing cost is high ( Audrin et al, 2019 ). However, for the high noise levels for the L Amax indicator (65–70 and 70–75 dB(A)), but also at lower noise levels for the L den and L dn indicators (50–55 dB(A)), noise contour areas being greater, within these zones there are certain central neighbourhoods of the Island of Montréal (Villeray–Saint-Michel–Parc-Extension, Côte-des-Neige-Notre-Dame-de-Grâce), as well as surrounding neighbourhoods (Saint-Léonard, Lachine and Ahuntsic-Cartierville), where we find, at least in some parts of these territories, a high proportion of the low-income population ( Ades et al, 2012 , Séguin et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the work conducted on aircraft noise, transversal studies have shown that low-income households and certain ethno-cultural communities (Hispanic, Black, or Asian) are subject to disproportionate exposure to high levels of aircraft noise in their residential area. This was shown in Saint-Louis (United States) ( Most et al, 2004 ), Phoenix (United States) ( Sobotta et al, 2007 ), Calgary and Vancouver (Canada) ( Audrin et al, 2019 ) and across the United States (US) ( Collins et al, 2020 ). For example, Sobotta et al (2007) find that on average in Phoenix, the percentage of Hispanic households increases the probability of being exposed to high levels of aircraft noise by 25%.…”
Section: Literature Reviewmentioning
confidence: 94%
See 3 more Smart Citations